Effects of Dinarmus basalis (rendani) on the population density of Callosobruchus maculatus (fabricius) on stored cowpea (Vigna unguiculata walp) seeds - B.N. Iloba (Tropical and Subtropical Agroecosystems, 2007)
The control of Callosobruchus maculatus F. oncowpea seeds was studied in the laboratory usingDinarmus basalis as parasitoid. Five males andfemales adult C. maculatus were allowed to ovipositonto ten sets of cowpea seeds each set weighed 5g.Five males and females D. basalis were introduced atthree days intervals (beginning from the 6th day afteroviposition) into each of the nine sets that had beeninfested with eggs of C. maculatus contained inspecimen bottles. No D. basalis was introduced intothe tenth set of cowpea seeds and this served ascontrol. No differences were observed in the numberof eggs laid per female C. maculatus in all the sets (P>0.05) and this ranged from 37.80 - 41.20. Nodifferences were observed on adult C. maculatus thatemerged when D. basalis was introduced at the 6th, 9 thand 12th day after oviposition (DAO) (P> 0.05).Percent emergence was 0.59, 0.53 and 1.85% at 6, 9and 12th day, respectively. C. maculatus emergenceincreased from 67.81% in the treatment that wasinoculated on the 21st DAO to 74.48 when inoculationwas done on the 30th day. The total D. basalis perfemale in each culture was 12.81% on the 6th day to17.56% on the 15th day and decreased significantly to11.78% when inoculation was done on the 30th day.The observed percentage mortality of C. maculatusincreased from 25.03% to 99.41% on the parasitisedculture when compared to 25.52 in the control.Introduction of D. basalis during the larval stage of C.maculatus caused higher mortality of the pest and littleor no effect on the adult C. maculatus.